A study of turnover intention and exit choice among the registered nurses in the private hospitals in Peninsular Malaysia / Tang Wai Mun - Tang, Wai Mun (2018)
The study aimed to investigate the Peninsular Malaysian private hospital nurses’ turnover intention and exit choice. Furthermore, the study aimed to determine the nurses’ perceptions towards their nursing practice environment, professional commitment, and organisational commitment. Subsequently, the relationships among the variables were examined based on a conceptual framework constructed for the study. The study was a quantitative, cross-sectional inferential survey study. The participants of the study were private hospital registered nurses. The sampling of the study consisted of two phases: hospital sample was selected through simple random sampling while; nurse sample was selected through convenience sampling. A total of 820 participants (response rate 64%) from four private hospitals took part in the study. The statistical analyses consisted of ttest, hierarchical multiple regression, and partial correlation. In general, the analysis revealed moderate intent of turnover. Inter-organisational turnover intention was found to be the highest, while professional turnover intention was the lowest. As for exit choice, nursing related exit choices such as advancing in nursing education, practicing nursing in another country and organisation were the most preferred choices. In addition, the practice environment of the private hospitals was perceived as favourable environment in which the environment supported professional nursing practice. Furthermore, professional and organisational commitments were found to be at moderate level. Professional commitment was higher than organisational commitment. Moreover, the results testified that nursing practice environment, exit choice, professional, and organisational commitments were significant predictors for the overall turnover intention after controlling the socio-demographic variables. Nonetheless, multilevel analysis of the different forms of turnover intention revealed distinctive sets of predictors for the different forms of turnover intention. The analysis for the relationship of nurses’ commitment and practice environment on turnover intention found that organisational commitment and practice environment were significant predictors for organisational turnover intention. The study revealed that professional commitment did not influenced organisational turnover intention. Country and professional turnover intention was not influenced by practice environment. Conversely, country turnover intention was exclusively influenced by organisational commitment while, professional commitment influenced professional turnover intention. On the other hand, the analysis for the relationship of nurses’ exit choice and practice environment on turnover intention revealed that nurses’ exit choice (regardless nursing or non-nursing related exit choice) and nursing practice environment were significant predictors for organisational and country turnover intention. Furthermore, non-nursing related exit choice was the predictor for professional turnover intention. Nevertheless, commitment and exit choice did not demonstrate mediating effect in the relationship between nursing practice environment and turnover intention. In conclusion, the research findings clearly indicated the presence of turnover intention among the Peninsular Malaysian private hospital nurses. Nursing practice environment, commitment and exit choices were significant predictors of turnover intention. Henceforth, relevant and appropriate interventions towards improving practice environment and commitment were strongly recommended in order to reduce turnover intention. Furthermore, findings of exit choices were crucial in providing the direction towards nursing recruitment and retention strategies.